Recovery of phosphate from dewatered anaerobic sludge and wastewater by thermally treated P.oceanica residues and its potential application as a fertilizer - Photiou, Panagiota; Vyrides, Ioannis (My University, 2021)
A process for the valorization of seagrass residues has been developed, aiming to investigate its potential as a phosphate adsorbent and the production of added-value products, which can be assessed in agricultural applications. Posidonia oceanica residues were thermally treated (500 °C, 1 h) and were tested as an adsorbent of phosphate from real wastewater. Chemical leaching experiments of phosphate from dewatered anaerobic sludge (DWAS) were conducted, evaluating sonication and inorganic acids (sulfuric acid (SA), thermal-sulfuric acid (TSA), and nitric acid (NA)) as extraction methods. Τhe extraction efficiency of each method tested demonstrated that the most suitable acid medium to leach out phosphate were SA and TSA processes with 84.9 and 93.2% removal efficiency, respectively. Moreover, the saturation capacity of thermally treated P. oceanica was assessed, and the results confirmed the high phosphate adsorption capacity (179.1 mg g-1). Adsorption batch experiments with real wastes (anaerobic effluent wastewater and leached solution from DWAS), demonstrated that thermally treated seagrass could have a high adsorption efficiency and selectivity towards phosphate. After phosphate adsorption, the solid residues were mixed with compost in different ratio and then tested as fertilizer substitutes on plant growth. The solid residue after adsorption produced from anaerobic effluent or synthetic solutions imposed a positive effect on plant growth with germination index (GI) values 96.7-111.14%, for all types of seeds tested (Solanum Lycopersicum, Lepidium sativum, and Sinapis alba), while the solid residue after adsorption produced from DWAS leached solution negatively affected the germination of plants, probably due to potentially refractory compounds contained in DWAS.
Keywords: Adsorption; Anaerobic wastewater effluent; Dewatered sludge; P. oceanica residues; Phosphates; Plant growth